Industrial/organizational psychology an applied approach - Aamodt, Michael G. (Cengage Learning, 2016)
Striking a balance between research, theory, and application, the eighth edition of this text helps students discover the relevance of industrial/organizational psychology in everyday life through practical application. The book guides students in analyzing topics such as resume writing, interview survival, job description authoring, performance appraisal, employment law, job satisfaction, work motivation, and leadership. Humor, case studies, real-world examples, and a friendly writing style make the book both accessible and interesting. Numerous charts, tables, flowcharts, and exercises help students conceptualize complex issues.